2015
DOI: 10.1089/jpm.2014.0387
|View full text |Cite
|
Sign up to set email alerts
|

Methadone for Patients with Malignant Psoas Syndrome: Case Series of Three Patients

Abstract: Methadone may be considered a treatment choice for MPS patients in whom pain is difficult to control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 15 publications
(27 reference statements)
0
42
0
Order By: Relevance
“…However, this treatment often fails to manage pain because of insufficient response from the complex nature of the pathophysiology of MPS, movement‐related worsening of pain due to MPS, and enhanced adverse events (eg, drowsiness) because of the combined use of multiple analgesics . In fact, multimodal analgesic treatment for pain due to MPS with or without concurrent anticancer treatments (chemotherapy and radiotherapy) is reported to have achieved good pain control in 7 of 12 cases (Table ), suggesting that a significant number of MPS cases did not achieve sufficient pain control. Switching the opioid administration route to the spinal route may contribute to reducing the adverse events from systemic opioids by decreasing the total amount of opioid administered .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this treatment often fails to manage pain because of insufficient response from the complex nature of the pathophysiology of MPS, movement‐related worsening of pain due to MPS, and enhanced adverse events (eg, drowsiness) because of the combined use of multiple analgesics . In fact, multimodal analgesic treatment for pain due to MPS with or without concurrent anticancer treatments (chemotherapy and radiotherapy) is reported to have achieved good pain control in 7 of 12 cases (Table ), suggesting that a significant number of MPS cases did not achieve sufficient pain control. Switching the opioid administration route to the spinal route may contribute to reducing the adverse events from systemic opioids by decreasing the total amount of opioid administered .…”
Section: Discussionmentioning
confidence: 99%
“…MPS often affects patient quality of life (QOL) as extension of the ipsilateral hip joint exacerbates pain, resulting in difficulty in walking or lying down in the supine position. Although a recent case report suggested methadone has utility in alleviating the pain associated with MPS, multimodal pain management regimens, including systemic opioid analgesics, non‐opioid analgesics, and adjuvant analgesics, often fail . Although neuraxial analgesia is a well‐recognized analgesic option in patients with severe pain refractory to systemic opioids or accompanied by significant side effects from systemic opioids, to the best of our knowledge, only 1 case of MPS with successful pain control using neuraxial analgesia has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…A simple analgesic agent is often ineffective, and multimodal pharmacotherapy, including opioids, non-opioid analgesics, and adjuvant drugs (antiepileptics, antidepressants, and muscle relaxants), is required, although its effectiveness has been shown to be limited (2,3). Recent studies have shown that rotation switching of opioids to methadone was effective for refractory neuropathic pain (6,20). Other studies reported the efficacy of intervention strategies, including epidural analgesia (9,19), injection from a psoas sheath catheter (21) or intrathecal catheter (19,22), and dorsal rhizotomy (23).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…The average time until symptom improvement was 2.3 days after methadone treatment (95% CI 1.86, 2.80). Based on these observations, methadone is considered as a valuable therapeutic agent for MPS patients ( Takase et al, 2015 ).…”
Section: Methadone For the Treatment Of Cancer-related Painmentioning
confidence: 99%